Mastering Your PhD Survival and Success in the Doctoral Years and Beyond - Gosling, Patricia; Noordam, Lambertus D. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
"Mastering your PhD" helps guide PhD students through their graduate student days. Filled with practical advice on getting started, communicating with your supervisor, staying the course, and planning for the future, this book is a handy guide for graduate students who need that extra bit of help getting started and making it through. Every year, thousands of students around the world embark on the long and difficult journey toward a PhD. Some of these students will make it through their program with flying colors. Others will experience difficulty getting to the end: some will sink and some will manage to swim - barely. The doctoral years can be daunting. While mainly directed to PhD students in the sciences, the book's scope is broad enough to encompass the obstacles and hurdles that almost all PhD students face at some point in their doctoral training. Who should read this book? Students of the physical and life sciences, computer science, math, and medicine thinking about entering a PhD program, doctoral students at the beginning of their research and any graduate student who is feeling frustrated and stuck. It's never too early or too late! "A must for any student in natural science who is doing or is considering doing a PhD. Also, I strongly recommend PhD supervisors to read this book -- they will learn a lot." --Henrik Stapelfeldt, Professor of Chemistry, Arhus Denmark "At last, a book about graduate study that paints the big picture and that recognizes PhD work as a real job involving many of the same relationship and business issues that will be important to students throughout their careers. Outstanding!" -- Lou Bloomfield, Professor of Physics, University of Virginia, USA.